1993
DOI: 10.1111/j.1467-9280.1993.tb00586.x
|View full text |Cite
|
Sign up to set email alerts
|

A Neural System for Error Detection and Compensation

Abstract: Humans can monitor actions and compensate for errors. Analysis of the human event-related brain potentials (ERPs) accompanying errors provides evidence for a neural process whose activity is specifically associated with monitoring and compensating for erroneous behavior. This error-related activity is enhanced when subjects strive for accurate performance but is diminished when response speed is emphasized at the expense of accuracy. The activity is also related to attempts to compensate for the erroneous beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

145
2,371
34
13

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,570 publications
(2,563 citation statements)
references
References 23 publications
145
2,371
34
13
Order By: Relevance
“…Three recent studies have provided brain-behavior relationships to support such a hypothesis Gehring et al, 1993;Kerns et al, 2004), indicating that strategic processes following an error, namely adapting response speeds on the trials immediately following an error, correlated with greater activity in the ACC region during the error trial. Implementation of the increased cognitive control was related to greater dorsolateral prefrontal cortex activity (dPFC).…”
Section: Introductionmentioning
confidence: 98%
“…Three recent studies have provided brain-behavior relationships to support such a hypothesis Gehring et al, 1993;Kerns et al, 2004), indicating that strategic processes following an error, namely adapting response speeds on the trials immediately following an error, correlated with greater activity in the ACC region during the error trial. Implementation of the increased cognitive control was related to greater dorsolateral prefrontal cortex activity (dPFC).…”
Section: Introductionmentioning
confidence: 98%
“…Gehring et al, 1993;Hewig, Coles, Trippe, Hecht, & Miltner, 2011;Scheffers & Coles, 2000;Shalgi & Deouell, 2012). However, many other studies show no relationship between ERN and error awareness (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…They found a modulation of auditory N1 amplitude, possibly reflecting auditory attention: increased amplitude following the positive shifts but reduced amplitude after the negative shifts. Interestingly, the error-related negativity (ERN; Gehring et al, 1990;Gehring et al, 1993) in averaged ERPs occurred around 200 ms after a positive shift, with a current source located in the medial prefrontal cortex, but no ERN was identified after a negative shift. The ERN is an ERP component that appears after the 6 execution of errors (Gehring et al, 1990;Gehring et al, 1993) and has been suggested to be associated with N2 (Praamstra et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the error-related negativity (ERN; Gehring et al, 1990;Gehring et al, 1993) in averaged ERPs occurred around 200 ms after a positive shift, with a current source located in the medial prefrontal cortex, but no ERN was identified after a negative shift. The ERN is an ERP component that appears after the 6 execution of errors (Gehring et al, 1990;Gehring et al, 1993) and has been suggested to be associated with N2 (Praamstra et al, 2003). Determining whether or not these ERP components reflect the error correction mechanism itself or are associated with post-error processing (i.e., conscious awareness of errors) requires further investigation.…”
Section: Introductionmentioning
confidence: 99%